Ancient Starch Remains Reveal the Vegetal Diet of the Neolithic Late Dawenkou Culture in Jiangsu, East China - Zhang, Xi; Zhu, Xiaoting; Hu, Yingfang; Zhou, Zhenyu; Olsen, John W.; Guan, Ying (Frontiers in Ecology and Evolution, 2021)
Abstract: The Liangwangcheng site, located in Pizhou County, Xuzhou City, northern Jiangsu Province, is one of the most important Neolithic Dawenkou Culture archaeological sites in the Haidai area of China’s eastern seaboard. In recent years, archaeobotanical studies in the Haidai area, mainly focusing on Shandong Province, have yielded fruitful results, while relatively few such studies have been undertaken in northern Jiangsu Province. Here, we report the results of dental residue analysis conducted on 31 individual human skulls unearthed from the Late Dawenkou Culture Liangwangcheng site. The starch granules extracted from these residue samples indicate that foxtail and broomcorn millet, rice, roots and tubers, and legumes comprised the vegetal diet of Liangwangcheng’s occupants. Evidence suggests that mixed rice-millet agriculture played a definite role, with the coexistence of gathering as an economic element. According to archaeobotanical evidence from surrounding cotemporaneous sites, the Late Neolithic human groups that lived in the lower Huang-Huai River drainage shared similar subsistence patterns. Our results provide new evidence for a more comprehensive understanding of plant resource utilization and agricultural development in northern Jiangsu during the Dawenkou period.